Composición por tallas, edad y crecimiento de Litopenaeus vannamei (Natantia: Penaeidae), en la laguna Mar Muerto, Oaxaca-Chiapas, México - Ramos-Cruz, Sebastián (2000)
The commercial catches of white shrimp Litopenaeus vannamei were sampled (May through November 1996) in the Mar Muerto lagoon located between Oaxaca and Chiapas states, Mexico. To measure it’s growth rate at the innermost portions of this system, 16 378 length and weight records were obtained. Length fluctuated between 11 and 145 mm, and weights between 0.1 and 26.3 g. The minimum mean size for recruitment to the exploited phase is 45 mm. Organisms leave the lagunar system for recruitment to the marine zone 83-120 mm/length, at an age of 1.5 - 4.5 months. Analysis of modal progression detected 13 generations inside the lagoon. The growth rates ranged between 0.13 and 1.27 mm/day, with a mean of 0.64 mm/day. The asintotic lengths fluctuated between 105 and 159 mm with a mean of 136 mm, while the asintotic weight fluctuated between 8 and 23 gr with a mean of 15 gr. The parameters of the von Bertalanfy growth model are: L∞ = 136 mm, P∞ = 15 gr, k = 0.0161 mm and to = 5 mm. Both, L∞ and P∞ doesn’t represent, at least in this case, the asintótics sizes and weights that the specie reache inside the system, but should be interpret like the means sizes and weight that should have the organisms at the time to leave it.